Pseudo-buried Barrett’s post radiofrequency ablation for Barrett’s esophagus, with or without prior endoscopic resection - Pouw, Roos E.; Visser, Mike; Odze, Robert D.; Sondermeijer, Carine M.; Kate, Fiebo J. W. ten; Weusten, Bas L. A. M.; Bergman, Jacques J. (Endoscopy, 2014)
Background and study aim: In our experience, biopsies from small residual islands of nonburied Barrett’s mucosa after radiofrequency ablation (RFA) are occasionally reported by pathologists to contain “buried Barrett’s” upon histological evaluation, despite the fact that these islands of columnar mucosa were visible endoscopically. The aim of this study was to evaluate the frequency of buried Barrett’s in biopsies obtained from small residual Barrett’s islands ( < 5 mm) sampled post-RFA, compared with biopsies from normal neosquamous epithelium. Patients and methods: Biopsies obtained from normal-appearing neosquamous epithelium and from small Barrett’s islands ( < 5 mm) in 69 consecutive Barrett’s patients treated with RFA were evaluated for the presence of buried columnar mucosa. Results: A total of 2515 biopsies were obtained from neosquamous epithelium during follow-up post-RFA. Buried glands were found in 0.1 % of biopsies from endoscopically normal neosquamous epithelium. However, when small islands of columnar mucosa were biopsied, buried glands were detected in 21 % of biopsies. Conclusion: To avoid accidental sampling of small islands resulting in a false-positive histological diagnosis of buried Barrett’s, thorough inspection should be performed before obtaining biopsies during post-RFA follow-up.